2011
DOI: 10.5535/arm.2011.35.6.772
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Scale for the Assessment and Rating of Ataxia (SARA) in Ataxic Stroke Patients

Abstract: ObjectiveTo examine the usefulness of the Scale for the Assessment and Rating of Ataxia (SARA) in ataxic stroke patients.MethodThis was a retrospective study of 54 patients following their first ataxic stroke. The data used in the analysis comprised ambulation status on admission and scores on the SARA, the Korean version of the Modified Barthel Index (K-MBI) and the Berg Balance Scale (BBS). The subjects were divided into four groups by gait status and into five groups by level of dependency in activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 6 publications
2
27
0
7
Order By: Relevance
“…The patient's original symptoms were coma, ataxia, and dysarthria. According to the SARA results and the findings of Kim et al, 6) the patient was predicted to be independent in basic ADLs and indoor gait using a cane. The results indicate that post-acute rehabilitation for acute lithium toxicity can improve ataxia and ADLs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The patient's original symptoms were coma, ataxia, and dysarthria. According to the SARA results and the findings of Kim et al, 6) the patient was predicted to be independent in basic ADLs and indoor gait using a cane. The results indicate that post-acute rehabilitation for acute lithium toxicity can improve ataxia and ADLs.…”
Section: Discussionmentioning
confidence: 85%
“…In a previous assessment of the usefulness of SARA, Kim et al observed that independent gait, Q-cane gait, and walker gait were correlated with SARA scores of 8 or lower, >8 to 11.5, and >11.5 to 12.25, respectively. 6) In addition, Kim et al's analysis of performance of ADLs showed that minimal dependence, moderate dependence, maximal dependence, and total dependence correlated with SARA scores of 5.5 or lower, >5.5 to 10.0, >10.0 to 14.25, and 23 points or higher, respectively. 6) To evaluate dysmetria while writing, the authors used the Runs test, line drawing tests, and circle drawing test.…”
Section: Physical Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies on the usefulness of SARA have been conducted to compare it with the existing ICARS and Barthel Index in cerebellar ataxia patients [ 9 ]. Kim et al [ 10 ] reported that SARA is useful in ataxic stroke patients and showed a significant correlation with the Modified Barthel Index, Berg Balance Scale, and gait status. Thus, SARA has been proven helpful in predicting the dependency of ADL and gait status and developing treatment plans [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients signed an informed consent authorizing an in‐depth review of their clinical history including medical problems and reproductive issues as well as a physical evaluation that included the use of standardized rating scales and interview‐based measures, specifically, the Scale for the Assessment and Rating of Ataxia (SARA) (Schmitz‐HĂŒbsch et al, 2006), and the Fahn‐Tolosa‐MarĂ­n Clinical Rating Scale for Tremor (FTM) (Fahn et al, 1993) to assess neurological findings during the exam of those carriers older than 50 years of age (n = 14). SARA is a valid clinical rating scale administered by the physician that has proven to be significantly correlated with results obtained using the International Cooperative Ataxia Rating Scale (ICARS) (Yabe et al, 2008) and the Modified Barthel Index (MBI) (Weyer et al, 2007; Kim et al, 2011). FTM is the most commonly used scale to evaluate essential tremor; it assesses postural, kinetic and rest tremor (Ondo et al, 2018).…”
Section: Methodsmentioning
confidence: 99%